Why Do Countries Peg the Way They Peg? : The Determinants of Anchor Currency Choice - Oomes, Nienke; Meissner, Christopher (Washington, D.C. : International Monetary Fund, 2008)
What determines the currency to which countries peg or "anchor" their exchange rate? Data for over 100 countries between 1980 and 1998 reveal that trade network externalities are a key determinant. This implies that anchor currency choice may well be suboptimal in that certain currencies, e.g., the U.S. dollar, could be oversubscribed. It also implies that changes in anchor choices by a small number of countries can have large and rapid effects on the international monetary system. Other factors found to be related to anchor choice include the symmetry of output shocks and the currency denomination of liabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet